Scale Alpha and Beta of Quantitative Convergence and Chemical Reactivity Analysis in Dual Cholinesterase/Monoamine Oxidase Inhibitors for the Alzheimer Disease Treatment Using Density Functional Theory (DFT). (22nd December 2013) - Morales-Bayuelo, Alejandro; Baldiris, Rosa; Vivas-Reyes, Ricardo
Abstract : Molecular quantum similarity descriptors and Density Functional Theory (DFT) based reactivity descriptors were studied for a series of cholinesterase/monoamine oxidase inhibitors used for the Alzheimer's disease treatment (AD). This theoretical study is expected to shed some light onto some molecular aspects that could contribute to the knowledge of the molecular mechanics behind interactions of these molecules with acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE), as well as with monoamine oxidase (MAO) A and B . The Topogeometrical Superposition Algorithm to handle flexible molecules (TGSA-Flex) alignment method was used to solve the problem of the relative orientation in the quantum similarity (QS) field. Using the molecular quantum similarity (MQS) field and reactivity descriptors supported in the DFT was possible the quantification of the steric and electrostatic effects through of the Coulomb and Overlap quantitative convergence scales (alpha and beta). In addition, an analysis of reactivity indexes is development, using global and local descriptors, identifying the binding sites and selectivity in the (cholinesterase/monoamine oxidase) inhibitors, understanding the retrodonor process, and showing new insight for drugs design in a disease of difficult control as Alzheimer.